Effectiveness of the Discovery Learning Model on the Ability to Write Short Stories based on Daily Events of Phase F XI Students at SMA N 7 Padang - Rahayu, Anggia Septi; Yulianti, Upit; Helda, Trisna (Pelangi (e-Journal), 2024)
This research was motivated by the low ability of students to write short stories which was influenced by several factors. First , students do not understand well what is done in the short story. Second , it is difficult for students to arrange words into good and correct sentences, this is due to a lack of ideas when writing short stories. Third , students' lack of interest in education and thinking makes it difficult to determine topics that will be developed as short stories. This research aims to describe the effectiveness of the discovery learning model on the ability to write short stories based on daily events of Phase F XI students at SMA Negeri 7 Padang. This type of research is quantitative with experimental methods. The design of this research is One Group Pretest-Posttest Design . The population in this study were Phase F XI students of SMA Negeri 7 Padang. The variables of this research are the use of the discovery learning model as the independent variable and the ability to write short stories as the dependent variable. The data for this research are the scores from students' short story writing performance tests. The results of this research are First , the ability to write short stories based on daily events of Phase F XI students at SMA Negeri 7 Padang before using the discovery learning model (pretest)